SPATIO TEMPORAL DISTRIBUTION OF SMALL PELAGIC FISH IN THE JAVA SEA - Wijopriono Wijopriono (Indonesian Fisheries Research Journal, 2008)
Time spent in seeking fish schools and potential fishing areas is the main source of fuel consumption, and it is a significant factor in raising the cost of fishing operation. Therefore, knowledge of the distribution pattern lnd aggregations of commercial fish in space and time is of considerable financial value to the fishers anAlisnlng industry because it will assist them to reduce the time and fuel consumption of the boats in locating the rich fishing grounds.